IMPLEMENTASI KEBIJAKAN PENERIMAAN PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA (PPPK) GURU SD HONORER DI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN BANYUASIN - Dona, Rahma; Ahyani, Nur; Fulkan, Nuril (Universitas Lampung, 2024)
This study aims to describe the implementation of the government employee recruitment policy with work agreement (PPK) for honorary elementary school teachers in the Education and Culture Office of Banyuasin Regency. Qualitative research method with research subjects including Head of Education Office, Head of Regional Personnel Agency, Head of GTK/PTK Division, Head of Section, Principal and Elementary School Teacher. Data analysis uses source triangulation, technical triangulation, and member check triangulation. The results of the study indicate that describing the implementation of the government employee recruitment policy with a work agreement (PPK) for honorary elementary school teachers at the Banyuasin Regency Education and Culture Office in terms of bureaucratic structure, resources, communication in the implementation of the PPK recruitment policy and diapsospdi runs well. Inhibiting factors include aspects of facilities and infrastructure such as computers that are not functioning, disrupted internet network signals, and server errors. This study recommends improving communication, allocating adequate resources, strengthening commitment to school principals, and enforcing transparency in policy implementation. Penelitian ini bertujuan untuk mendeskripsikan implementasi kebijakan penerimaan pegawai pemerintah dengan perjanjian kerja (PPK) guru SD honorer di Dinas Pendidikan dan Kebudayaan Kabupaten Banyuasin. Metode penelitian kualitif dengan subjek penelitian meliputi Kepala dinas pendidikan, Kepala Badan Kepegawaian Daerah, Kepala Bidang GTK/PTK, Kepala Seksi, Kepala Sekolah dan Guru SD. Analisis Data menggunakan triangulasi sumber, triangulasi teknik, dan triangulasi member check. Hasil penelitian menunjukkan bahwa mendeskripsikan implementasi kebijakan penerimaan pegawai pemerintah dengan perjanjian kerja (PPK) guru SD honorer di Dinas Pendidikan dan Kebudayaan Kabupaten Banyuasin dari segi struktur birokrasi, sumber daya, komunikasi dalam implementasi kebijakan penerimaan PPK dan diapsospdi berjalan dengan baik. Faktor penghambat melipusti aspek sarana dan prasarana seperti komputer yang tidak berfungsi, sinyal jaringan internet yang terganggu, dan server eror. Penelitian ini merekomendasikan untuk meningkatkan komunikasi, mengalokasikan sumber daya yang memadai, memberikan penguatan komitmen kepada kepala sekolah, dan menegakkan transparansi dalam implementasi kebijakan.